2015
DOI: 10.1371/journal.pone.0120148
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Cochlear Implant Strategy Based on a “Phantom” Channel

Abstract: Unbalanced bipolar stimulation, delivered using charge balanced pulses, was used to produce “Phantom stimulation”, stimulation beyond the most apical contact of a cochlear implant’s electrode array. The Phantom channel was allocated audio frequencies below 300Hz in a speech coding strategy, conveying energy some two octaves lower than the clinical strategy and hence delivering the fundamental frequency of speech and of many musical tones. A group of 12 Advanced Bionics cochlear implant recipients took part in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 44 publications
(53 reference statements)
1
34
0
4
Order By: Relevance
“…For example, FEM models are used to analyze simultaneous stimulation sound coding strategies (Kalkman et al, 2014, 2016). These strategies try to shape or focus the electrical field to be more focused and to produce different pitch sensations (Nogueira et al, 2009, 2015a). Patient-specific 3D volume conduction models can be used to optimize the parameters of the focusing and the current steering coefficients (Litvak et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, FEM models are used to analyze simultaneous stimulation sound coding strategies (Kalkman et al, 2014, 2016). These strategies try to shape or focus the electrical field to be more focused and to produce different pitch sensations (Nogueira et al, 2009, 2015a). Patient-specific 3D volume conduction models can be used to optimize the parameters of the focusing and the current steering coefficients (Litvak et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The fitting levels (loudness perception) depend not only on the current spread in the cochlea but also on the auditory nerve activity. As shown in this manuscript, the voltage predicted by the volume conduction model can be sampled at the auditory nerve positions and coupled to an auditory nerve model (Smit et al, 2008; Nogueira et al, 2015a,b). Such a model could be used to predict the loudness of sound and is a potential tool to speed up and objectivize the fitting procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study findings showed that CI users with greater apical stimulation reported sound quality ratings that more closely resembled their NH counterparts, suggesting superior sound quality perception. More recently, a sound processing strategy called partial bipolar stimulation emerged as means to expand low‐frequency range available to CI users 55, 56. Partial bipolar stimulation relies on current steering to create virtual “phantom” channels that extend beyond the physical end of an electrode array.…”
Section: Introductionmentioning
confidence: 99%
“…A study enrolling 12 post‐lingually deaf CI users compared Phantom stimulation to the standard Advanced Bionics HiRes Fidelity 120 processing strategy. Although there was no significant difference between Phantom and the control processing strategy for most components of the music questionnaire, Phantom CI users reported a statistically significant difference in improved sound balance and preferred listening to music using this strategy 55. In another recent study, Munjal et al51 utilized the CI‐MUSHRA to find that creation of a phantom electrode through partial bipolar stimulation allowed for superior (more normalized) sound quality perception relative to Fidelity 120 processing strategy.…”
Section: Introductionmentioning
confidence: 99%